The first application of epiluminescence dermoscopy in erythema nodosum - Antonio Chuh (Our Dermatology Online, 2018)
We reported an adult female with a clinical diagnosis of erythema nodosum. The patient declined lesional biopsy. We applied epiluminescence dermoscopy, which revealed features compatible with panniculitis. We managed conservatively. The rash remitted four weeks since rash onset, leaving only post-inflammatory hyperpigmentation. Dermoscopic examination cannot replace lesional biopsy for histopathology for a diagnosis of erythema nodosum to be properly confirmed. However, there are patients with clinical diagnoses of erythema nodosum who would not give consent for lesional biopsies, and patients presenting to dermatologists when the rash is already remitting. We thus described the dermoscopic findings of our patient in this report. The applicability of dermoscopy to patients with erythema nodosum and differential diagnoses of such is yet to be evaluated by further studies.